If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-x+7(5x-23)=9
We move all terms to the left:
-x+7(5x-23)-(9)=0
We add all the numbers together, and all the variables
-1x+7(5x-23)-9=0
We multiply parentheses
-1x+35x-161-9=0
We add all the numbers together, and all the variables
34x-170=0
We move all terms containing x to the left, all other terms to the right
34x=170
x=170/34
x=5
| 8+2c=c-8+3c | | -x.x+1=48 | | 2^x=118 | | -12x+9(x+2)=6(x-6)+9 | | 2n+3=48 | | x.x-1=48 | | -(9x-15)=87 | | x.x+1=48 | | -2-3=8+9v | | x-0.2x=150 | | 3y-5+9y=7+9y | | -8-2(-8p+10)=10+7p-2 | | −3x2+12x−120=0 | | -10z-10=10-8z | | 7(4x-3)=-217 | | 400-2a=224 | | 6=x-2+10 | | 3(1+7a)=-81 | | -6(-4x+2)=-132 | | 200000=0.2*x | | 4(y–3)=-5y+51 | | 0.602=j-75 | | (5x*5x)+43=(x-1)(5x+6) | | 9x+3(52x)=15(x+1) | | m/42=-26 | | -5(1+5x)=-230 | | 200,000=0.2*x | | 0=12x^2-20x+6 | | 3-2x/4= | | 6=20-2/3x | | Y=25x-50 | | -5(x+6)-18x=-5(x+9)-3 |